PENGARUH BRAND AMBASSADOR, BRAND AWARENESS, DAN VIRAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE SAMSUNG PADA 17 AGUSTUS 1945 SURABAYA - Yeni Mustika Sari; Ida Ayu Nuh Kartini (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This study aims to determine the influence of brand ambassadors, brand awareness and viral marketing on purchasing decisions for Samsung Smartphone products. This study is expected to provide clear insight into the factors that influence purchasing decisions, so that it can be a strategic guide for companies in formulating more efficient and targeted marketing strategies. This study uses a quantitative method, with a population of 11,312 students at the University of 17 Agusutus 1945 Surabaya. The sampling technique uses the Slovin formula with a sample size of 100 respondents. The type of data used is quantitative data, derived from primary data sources using a questionnaire. The distribution of questionnaires via google form. The instrument test in this study is a validity test and a reliability test. The data analysis used is multiple linear regression analysis with hypothesis testing using the t test and F test and the coefficient of determination (R2). The data is processed using SPSS 26. The results of the study show that all indicators are valid and reliable. The results of the T test state that brand ambassadors, brand awareness and viral marketing have a significant effect on purchasing decisions. The results of the F test state that brand ambassadors, brand awareness and viral marketing have a simultaneous effect on the purchase decision of Samsung Smartphone products. While the results of the R² test show that the influence of the independent variable on the dependent variable is 59.3% while the remaining 40.7% is influenced by other variables outside the research model.